2019
DOI: 10.1177/0391398819864368
|View full text |Cite
|
Sign up to set email alerts
|

Sodium loss, extracellular volume overload and hypertension in peritoneal dialysis patients treated by automated peritoneal dialysis cyclers

Abstract: Introduction: Achieving sodium balance is important for peritoneal dialysis patients, as sodium excess may lead to hypertension and extracellular water expansion. We wished to determine whether greater sodium removal had adverse consequences. Methods: We calculated 24-h urinary and peritoneal sodium losses in peritoneal dialysis patients treated by automated cyclers, when attending for peritoneal membrane and bioimpedance assessments. Results: We reviewed 439 peritoneal dialysis patients, 56.7% male, average a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Peritoneal sodium removal was also associated with the volume of icodextrin prescribed, supporting other studies which have shown that volume status is better maintained with icodextrin compare to 22.7 g/L glucose exchanges [26]. Whereas some smaller earlier studies did not demonstrate an effect of hypertonic glucose dialysates and peritoneal sodium losses [9], we noted a univariate association, which would be expected as hypertonic dialysates would be expected to increase ultrafiltration [10, 24]. There was a weak association between higher mean arterial blood pressure and lower peritoneal sodium losses, and previous studies have either reported a similar association or no effect of peritoneal sodium losses on blood pressure [9, 27].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Peritoneal sodium removal was also associated with the volume of icodextrin prescribed, supporting other studies which have shown that volume status is better maintained with icodextrin compare to 22.7 g/L glucose exchanges [26]. Whereas some smaller earlier studies did not demonstrate an effect of hypertonic glucose dialysates and peritoneal sodium losses [9], we noted a univariate association, which would be expected as hypertonic dialysates would be expected to increase ultrafiltration [10, 24]. There was a weak association between higher mean arterial blood pressure and lower peritoneal sodium losses, and previous studies have either reported a similar association or no effect of peritoneal sodium losses on blood pressure [9, 27].…”
Section: Discussionsupporting
confidence: 86%
“…These patients had greater residual renal function and urinary sodium losses, thus over-all losses were similar between modalities, supporting the results of smaller studies [10, 24]. As with many centres we practice incremental dialysis, with peritoneal dialysis prescriptions taking into account residual renal function [25], and as such patients with greater residual renal function and urinary sodium losses had correspondingly lower peritoneal sodium losses.…”
Section: Discussionmentioning
confidence: 63%
“…[24,25] Earlier studies reported that PD technique failure was more common for fast transporters, but this risk was reduced or reversed with the introduction of APD cyclers in combination with the liberal use of icodextrin. [26,27] We noted lower peritoneal sodium removal to glucose absorption when patients did not use icodextrin, irrespective of whether they used CAPD or APD and CCPD. On multivariable analysis treatment with APD remained a significant factor associated with lower peritoneal sodium removal and higher glucose absorption, but this is most likely due to not using icodextrin.…”
Section: Discussionmentioning
confidence: 88%